Application of SWOT Analysis for Optimizing the Process of an Automotive Services Company - Mesquita Padilha, Oéssimo; Tregue Costa, Alexandra Priscilla; Barbosa de Alencar, David; Estanislau Sanches, Antônio (International Journal for Innovation Education and Research, 2019)
Every entrepreneur or entrepreneur has as his main dream to see his business flow and gain successful proportions in the environment where it operates and for that to happen, there are countless researches, analyzes, studies, patience and an unending dedication to stand out and achieve. the desired success. Within a company, the person in charge or the owner of your business analyzes with a broad view, whether external or internal, its weaknesses and strengths. In order to remain in the market, the automotive accessories sales and retail sector adopts a set of systemic mechanisms that use methodological processes within a context, set goals, undertake actions, mobilize resources. and decision making to achieve goals in order to achieve success. Analyzing the importance of organizational strategic planning in institutions or companies in a competitive market requires a refinement of quality tools within planning facets for a better understanding of the subject.